(untitled) (Plant Tissue Culture and Biotechnology, 2015)
The present research work reports the cytomorphological evaluation and an efficient protocol for in vitro micropropagation of an endemic, endangered and threatened herb Centella asiatica (L.) Urban (Mandukparni) from Himachal Pradesh, India. Plant species is a potent memory enhancer, antidiabetic, antioxidant, antimutagenic, anticancerous and also reported to have cardiovascular properties and used to cure chronic hepatitis disorders. Eight morphometric characters for each 10 different accessions were extensively studied, but no new morphotype was reported. As per the cytology, the present report (2n = 18) confirmed the earlier chromosome counts from India and abroad. As there is an important need to preserve this plant species and to make it available all over the year to pharmaceutical industries without causing loss of germplasm from the wild region, efficient in vitro micropropagation protocol through nodal explant has been developed. As per the results, the highest percentage of multiple shoot induction was 90.20 showing average 16.3 number of shoots on the medium augmented with 2.0 mg/l BAP + 0.5 mg/l Kn. Whereas, the combined concentration of 1.0 mg/l NAA + 1.0 mg/l IBA showed highest 92.2% root induction with average 16.5 number of roots per shoot. The survival rate of these plantlets under green house condition was 80%. This protocol can be used for further regeneration and genetic transformation studies in Centella Plant Tissue Cult. & Biotech. 24(2): 155-171, 2014 (December)